Evaluation of antioxidant and antimicrobial activities of pomegranate (Punica granatumLinn.) peel extracts - Tinrat, Sirikhwan; Singhapol, Chatchawan (Asia-Pacific Journal of Science and Technology, 2017)
Pomegranate fruit (Punicagranatum) is an edible medicinal plants which is an important source of phytochemical compounds. The highest of phenolics and flavonoids content were found in the peel acetone (25.60-+0.00 mg GAE/g DW) and 95% ethanol (33.44?0.05 mg RE/g DW) extracts, respectively. The highest antioxidant activities in the peel were shown in the 40% and 95% ethanol fractions (17.04?0.01 mg AAE/g DW) by DPPH method and in the acetone (25.60-+0.00 mg AAE/g DW) by the FRAP method. For antimicrobial activity ofpeel extracts, all peel extracts exhibited broad spectrum activity against all microorganisms with the MICsranging 0.390-25.00 mg/ml by broth macrodilution method. The acetone fraction of peel displayed the highest antimicrobial activity. Staphylococcus aureusATCC 1216 was the most sensitive strain to all extracts (MIC 0.390 mg/ml and MBC 1.562 - 6.250 mg/ml). Thus, pomegranate peel could serve as a potential source of antioxidants and antimicrobial agents for use as active ingredient in pharmaceutical formulations, food and cosmetic products.